Binary columnar transposition cipher (Al-Mansour Journal, 2022)
Cryptography is the way to keep our information safe from intruders. Transposition is a cipher technique that has been used historically to encrypt and decrypt messages. Stream and block cipher is a modern technique that has been used to deal with binary numbers. This paper uses the Columnar Transposition Cipher (CTC) method which is a type of transposition technique to enhance using the Block cipher technique. Using this combination of ciphers, makes the algorithm more complicated and secure. It makes it difficult for attackers to analyze the results and break the cipher.
Keywords: Cryptography; CTC; BCTC; Stream; Block; Transposition